AN EVALUATION OF THE MANAGEMENT OF PATIENTS WITH HYPOPARATHYROIDISM IN HOSPITAL PUTRAJAYA - Mui, Ng Yoke; Bin Abdul Onny, Muhammad Asyraf; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypoparathyroidism is a rare endocrine disorder characterized by hypocalcaemia, associated with an inappropriately low parathyroid hormone concentration. Since there is no Malaysian guideline for the management of hypoparathyroidism, we evaluated our management practice against published European guidelines. METHODOLOGY We reviewed the medical records of 36 patients aged 21–76 years old with hypoparathyroidism for at least one year, who were managed in the Internal Medicine and Endocrine Clinics of Hospital Putrajay. Data were obtained from the computerized clinical notes database and the pathology database. RESULTS It was found that the most common etiology of hypoparathyroidism was previous thyroidectomy (86.1%). Serum calcium and phosphate were measured at least annually in almost all patients (94.4%). Serum creatinine was checked at least annually in 94.4%. Serum vitamin D was measured in 61.1%. 24-hour urine calcium excretion was only checked in 25.0%. The target for calcium and phosphate was stated in only 2.8%. Calcium phosphate product was not documented for any of the patients. Kidney ultrasound was done in 22.2% and cataract screening was performed in 5.6%. Almost half of the patients (44.4%) were admitted for symptomatic hypocalcemia, and 16.7% developed renal impairment. Most patients (91.7%) were prescribed with calcium carbonate. Alfacalcidol was prescribed to 61.1%. None was on adjunctive treatment. CONCLUSION This study shows that the long-term outpatient monitoring and recording of hypoparathyroidism is inadequate in the local setting. We are therefore undertaking the task of constructing a checklist of relevant diagnostic and therapeutic procedures that will standardize management for this disease.